Geología de los cuadrángulos de Puerto Arturo, Flor de Agosto, San Antonio del Estrecho, Nuevo Perú, San Felipe, Río Algodón, Quebrada Airambo, Mazán, Francisco de Orellana, Huanta, Iquitos, Río Maniti, Yanashi, Tamshiyacu, Río Tamshiyacu, Buenjardín, Ramón Castilla, Río Yavarí-Mirín y Buenavista 4-p, 5-p, 5-q, 5-r, 6-p, 6-q, 6-r, 7-p, 7-q, 7-r, 8-p, 8-q, 8-r, 9-p, 9-q, 9-r, 10-9, 10-q y 10-r – [Boletín A 132] - Sánchez Fernández, Agapito Wilfredo (1999)
310 p., 19 mapas